2018
DOI: 10.3168/jds.2017-13364
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analyses based on a multiple-trait approach for modeling feed efficiency

Abstract: Genome-wide association (GWA) of feed efficiency (FE) could help target important genomic regions influencing FE. Data provided by an international dairy FE research consortium consisted of phenotypic records on dry matter intakes (DMI), milk energy (MILKE), and metabolic body weight (MBW) on 6,937 cows from 16 stations in 4 counties. Of these cows, 4,916 had genotypes on 57,347 single nucleotide polymorphism (SNP) markers. We compared a GWA analysis based on the more classical residual feed intake (RFI) model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…Estimates of SNP effects from single-step methods became available in 2012 [18,47]; however, a measure of significance for SNP estimates has not been available until now in current implementations of single-step GBLUP. Expanding the ideas from the equivalence between GBLUP and GWAS [2325], Lu et al [27] derived exact GWAS for a single-step GBLUP framework in a relatively small data set. In our study we showed exact p-values calculated for the first time using a large data set including genotypes, phenotypes, and pedigree.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Estimates of SNP effects from single-step methods became available in 2012 [18,47]; however, a measure of significance for SNP estimates has not been available until now in current implementations of single-step GBLUP. Expanding the ideas from the equivalence between GBLUP and GWAS [2325], Lu et al [27] derived exact GWAS for a single-step GBLUP framework in a relatively small data set. In our study we showed exact p-values calculated for the first time using a large data set including genotypes, phenotypes, and pedigree.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, Lu et al [27] showed that the same logic used in [2325] can be used in a SSGBLUP context. Simply stated, to obtain a statistical test for the effect of a single marker, we only need estimates of the breeding values of genotyped animals and their sampling distribution, and this can be readily obtained from SSGBLUP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HS6ST3 (heparan sulfate 6-O-sulfotransferase) has been associated with residual feed intake (Yao et al 2013), body weight and size (Wang et al 2018), and the fatty acid profile of beef (de Lemos et al 2018). DOCK1 (dedicator of cytokinesis 1) has been reported as a candidate gene for carcass composition indicator traits (Silva et al 2019), marbling score (Ryu & Lee 2016), feed efficiency (Lu et al 2018) and body weight (Li et al 2018a;Reis Neto et al 2019). We identified nine SNPs corresponding to eight genes associated with yak CG at time of weaning.…”
mentioning
confidence: 99%